Deep Tech: Emerging opportunities in innovation and entrepreneurship - Priego, Laia Pujol; Wareham, Jonathan; Romasanta, Angelo; Rothe, Hannes (Proceedings of the International Conference on Information Systems, 2021)
Deep Tech is receiving increasing attention from investors and policy as a means to solve the most pressing societal challenges, leverage new business opportunities, and increase global economic growth. To respond to the increasing need to fundamentally understand deep tech and its implications for business and innovation policy, this PDW sets out to establish a shared understanding among information systems researchers of how we can build strong research within IS and with other management sub-disciplines. The PDW will start with a dynamic panel discussion among IS scholars with interests in deep tech from different perspectives in the disciplines (i.e. three broad themes), followed by semi-structured roundtable discussions with participants to shape emerging research opportunities for future deep tech research. The results of the workshop will be integrated into a joint statement that spells out the conceptual background of the topic and sheds light on future research directions.